Driving e-Wallet continuance usage intention: a survey among generation Alpha in Malaysia during COVID-19 pandemic / Ho Hong Ren, Mohd Remie Mohd Johan and Thilagavathi Muttu - Ho, Hong Ren; Mohd Johan, Mohd Remie; Muttu, Thilagavathi (Universiti Teknologi MARA, Perlis, 2024)
The COVID-19 outbreak has affected almost every aspect of human life particularly vulnerable group such as Generation Alpha. E-wallet has become increasingly essential to avoid the virus transmission. The pandemic has led to a remarkable increase in e-wallet transactions in Malaysia. However, the reason behind the rapid rise in e-wallet usage is not widely agreed upon. Due to a lack of study on this topic, this paper contributes to the knowledge gap by studying and examining the significant factors that influence private university students' continued usage intention to use e-wallet as a payment mechanism during the pandemic by incorporating constructs from Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), Technology Continuance Theory (TCT), and Health Belief Model (HBM) into an integrated model. The study employed a quantitative design using Pearson correlation analysis and multiple linear regression analysis to assess the relationship between the variables through SPSS application. The convenience sampling method was used to select about 378 respondents from private universities in Kuala Lumpur and Selangor, including UCSI University, Management & Science University, Asia Pacific University, HELP University, Taylor's University, Sunway University, and SEGi University. The results revealed that facilitating conditions, social influence, perceived usefulness, perceived COVID-19 risk, and price benefit has a significant and positive contribution towards e-wallet continuance usage intention among Generation Alpha in Malaysia during the pandemic. The practical implications for the government and the service providers from the present findings can be used to develop strategies to promote the continuous intention of e-wallet usage during the COVID-19 pandemic.